Granting and Using Annual Leave in Ethiopia: A Look at the Practice at the Teklehaimanot Plant of MOHA Soft Drinks S.C - Girma, Dejene Janka (Bahir Dar University Journal of Law, 2022)
AbstractThe current Ethiopian Labor Proclamation provides for a number of stipulations toregulate the relationship between employers and employees. These stipulations deal,among other things, with how annual leave can (should) be granted by employers andused by employees. This article explores the position of the Labor Proclamation inrespect of some vital issues pertaining to the granting and use of annual leave. It willalso examine how these issues are dealt with in practice by using the experience ofone company, MOHA Soft Drinks Industry S.C. at the Teklehaimanot Plant. Althoughthe practice at this Company may not be used to make generalizations about how otheremployers deal with the above issues, it can serve as a real eye-opener. The articleconcludes that the stipulations of the Labor Proclamation are not implemented as theyought to be and there are some deviations in practice.